Pengembangan Model Pembelajaran Picture And Picture untuk Pembelajaran Menulis Teks Deskripsi VII SMP Negeri 1 Kota Batu - Anggun Restu; Lis Susilawati; Rina Wijayanti; Endang Sumarti (Universitas Insan Budi Utomo, 2024)
This study was conducted with the aim of making students more active in learning, especially for class VII SMP Negeri 1 Kota Batu. The results of this study indicate that the Picture and Picture learning model developed has very good quality and is suitable for use in learning descriptive texts in class VII SMP Negeri 1 Kota Batu. This model was evaluated through three main aspects: language, material, and design, each of which obtained positive validation results. The language aspect received an average score of 88.88 and was classified as